2022
DOI: 10.22270/jddt.v12i5.5602
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Targeted Therapy for Colorectal Cancer

Abstract: One of the most common and deadly cancers in the world, colorectal cancer (CRC) caused around 881,000 melanoma deaths in 2018. The third most frequent cause overall cancer-related death worldwide is colorectal cancer (CRC). A difficult issue related to chemotherapy is the subsequent adverse effects brought on by the toxicity of conventional medications. Location-specific/targeted distribution of chemotherapeutic medicines precisely to the afflicted site of something like the colon in a foreseeable and reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The cationic lipid and cationic biodegradable polymer-based Nanoparticle are widely used in the gene delivery system 50 . The lipid and polymer-based non-viral carrier systems have various advantages like low immunogenicity, low toxicity absence of viral recombination low production cost 51 , but have some limitations like cytotoxicity, stability into the serum, high duration of gene expression and large particle size. The lipid-polymer hybrid Nanoparticle is a more reliable carrier for gene delivery than other carriers because these are biodegradable, stable and long-lived Nanoparticle vector delivery systems.…”
Section: Gene Deliverymentioning
confidence: 99%
“…The cationic lipid and cationic biodegradable polymer-based Nanoparticle are widely used in the gene delivery system 50 . The lipid and polymer-based non-viral carrier systems have various advantages like low immunogenicity, low toxicity absence of viral recombination low production cost 51 , but have some limitations like cytotoxicity, stability into the serum, high duration of gene expression and large particle size. The lipid-polymer hybrid Nanoparticle is a more reliable carrier for gene delivery than other carriers because these are biodegradable, stable and long-lived Nanoparticle vector delivery systems.…”
Section: Gene Deliverymentioning
confidence: 99%
“…Herbal Skin Care Products: Lavender Silk Soaps, Lotions creams, Body powder,Lavender Herbal body powder, Skin Care Creams [32][33][34][35] .…”
Section: Applications Of Herbal Products In Cosmeticsmentioning
confidence: 99%
“…Similarly, Amiot and Lairon and Butt and Sultan reported that about 30-40% chances of cancer can be prevented by adopting a proper physical and dietary lifestyle. Consumption of vegetables rich in dietary antioxidants has been linked to a lower risk of different types of cancer, especially the mouth, pharyngeal, esophageal, lung, stomach, and colon cancer 95,[124][125][126][127][128][129][130] .…”
Section: Fruits and Vegetable Phytochemicals And Cancermentioning
confidence: 99%
“…Among the various food plants, fruits and vegetables (FAV) are reported to have health-improving benefits [1][2][3] . Some FAV such as the citrus fruits (orange, grapefruit, lime, lemon), grapes, pomegranates, apples, dates, green and yellow vegetables (peppers), cabbage, strawberries, carrots, dark leafy greens, and banana [4][5][6] , have been known worldwide to contain antioxidants. A characteristic of antioxidants is that they exert both additive and synergistic effects in reducing the risk of chronic diseases [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%